Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1074/jbc.m112.356733
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the Pineal Gland

Abstract: Background: MicroRNAs have not been studied in the pineal gland, the source of circulating melatonin. Results:The pineal miRNA population is profiled; developmental and tissue-specific patterns are described. The data suggest miR-483 perturbs melatonin production by promoting destruction of the Aanat transcript. Conclusion: miR-483 plays a physiological role in controlling melatonin synthesis. Significance: Pathophysiological changes in pineal miR-483 could alter melatonin synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…Recent data show that the microRNA miRNA-483 suppresses pineal Aanat expression and exhibits an inverse developmental expression pattern with high levels early in development [120], thus suggesting that maturation of pineal physiology in addition to a specific composition of homeodomain transcription factors may also involve a timely controlled relief from suppressing microRNAs.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recent data show that the microRNA miRNA-483 suppresses pineal Aanat expression and exhibits an inverse developmental expression pattern with high levels early in development [120], thus suggesting that maturation of pineal physiology in addition to a specific composition of homeodomain transcription factors may also involve a timely controlled relief from suppressing microRNAs.…”
Section: Future Directionsmentioning
confidence: 99%
“…A previous study analyzed the light-induced transcriptome of the pineal gland of zebrafish and showed that miR-183 affects the mRNA level of aanat2, the key enzyme in melatonin synthesis (Ben-Moshe et al, 2014). It was also reported that miR-483 regulated the synthesis of melatonin by inhibiting Aanat in the pineal glands of rats (Clokie et al, 2012). Another study identified lncRNAs that are differentially expressed between day and night in the pineal glands of rats (Coon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Because the circRNAs mainly work by binding miRNAs and suppressing their function, we predicted the miRNAs with binding sites in circRNA sequences (Figure 4G). Among the identified miRNA-circRNA pairs, circMboat2 and circNlrp5-ps were predicted to be regulated by miR-483, which was shown to suppress Aanat, the enzyme critical for melatonin synthesis (Clokie et al, 2012). Therefore, these circRNAs may be involved in the regulatory network of pineal gland function such as melatonin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat pineal gland, several miRNAs were shown to be preferentially expressed relative to other organs or parts of the CNS [39]. While one of the enriched miRNAs, miR-125b , did not show substantial day/night differences, cycles of moderate amplitude were observed in a number of other cases, such as miR-143 and miR-124 .…”
Section: Melatonin Synthesizing Organs: Modulation Of Mrna Stabilimentioning
confidence: 99%